Creation and validation of a new index to predict pneumonia associated with ischemic stroke - Alexis Suárez Quesada; Alexis Álvarez Aliaga; Andrés José Quesada Vázquez (Medisur)
Background: pneumonia associated with ischemic stroke is the medical complication with the greatest impact in this group of patients, as it increases the risk of recurrence, decreases functional recovery and triples the number of deaths. Objective: to create and validate a new predictive index of pneumonia associated with ischemic stroke. Methods: 725 patients with a diagnosis of ischemic stroke, belonging to a prospective cohort, treated at the Carlos Manuel de Céspedes Provincial General Hospital in Bayamo, Granma province, were studied. The sample was randomly divided into a construction cohort with 509 patients for the creation of the index, and another validation cohort with 216 patients. A new quantitative index of four risk categories was obtained from the corresponding regression coefficients of each independent predictor. Results: the variables that contributed the highest score to the index were dysphagia (28), the NIHSS scale ≥ 12 points (24) and heart failure (22). The new index presented good discriminative capacity (area under the ROC curve = 0.94). In the validation sample, it showed better discrimination capacity, greater validity and reliability when compared with the international A2DS2 and ISAN indices. Conclusion: the new index created and validated allows to satisfactorily predict the development of pneumonia associated with ischemic stroke. It is a useful and safe tool for use in healthcare practice.